Globalisation and World's Poor Institutions, Inequality and Justice - JOHN HARRISS (Economic and Political Weekly June 9, 2001, 2001)
Globalisation is an extremely powerful ideology being projected as having no alternative. There is resistance, even if not coherent as yet. The practical basis for an alternative is to be seen in the progress being made in different parts of the world, often by left parties, to make a reality of deliberative democracy, as in the experiments with people's planning in Kerala or with participative budgeting in Porto Alegre in Brazil.